Karakteristik Endapan Timah Primer Pada Daerah Paku, Bangka Selatan, Kepulauan Bangka Belitung - Restiko, Favian Avila (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2024)
Geological mapping conducted in Desa Paku, Bangka Belitung Islands. The mapping aimed to determine the characteristics of primary tin deposits in the study area by examining the distribution of lithology, stratigraphic sequence, geological structure patterns, distribution of alteration mineralization, and potential natural resources. The study involved three stages: preliminary, data acquisition, and data analysis. The stratigraphy of the study area consists of three rock units, from oldest to youngest: Pemali phyllite lithodeme, Tanjunggenting sandstone unit, and Alluvial deposits. Geological structures include joints, faults, and bedding. Faults are divided into seven groups: right-lateral Bukit Panjang fault, left-lateral Bukit Panjang fault, left-lateral Bukit Baji fault, right-lateral Bukit Baji fault, left-lateral Pelawan fault, left-lateral Atiau fault, and normal Bukit Panjang fault. Study area are divided into five based on the formation temperature of minerals, from high to low temperature: Quartz ± Sericite, Quartz ± Tourmaline, Quartz + Sericite + Illite ± Dickite ± Halloysite ± Tourmaline, Quartz+Kaolin+Dickite ± Illite-smectite, Kaolin + Montmorillonite + Illite-smectite. Sn content varies based on geometry, sheeted vein (112-114 ppm) and lode (112-6.044 ppm). The highest Sn content in the sheeted vein (19,800 ppm) and (21,621 ppm), presented in hydrothermal breccia with disseminated cassiterite minerals in a WE direction.